Fecal microbiota transplantation to fight Clostridium difficile infections and other intestinal diseases. Issue 4 (1st October 2016) - Moelling, Karin; Broecker, Felix
ABSTRACT: We have analyzed fecal bacterial and viral communities of a patient with recurrent C. difficile infection (rCDI) who was cured by fecal microbiota transplantation (FMT). The "Zürich Patient" experienced immediate cure and has remained free of symptoms for now over 5 y. Donor-similar bacterial compositions after 4.5 y post-FMT demonstrated sustainable engraftment of donor microbiota predominated by Bacteroidetes and Firmicutes bacteria. Appearance of beneficial species Faecalibacterium prausnitzii and Akkermansia municiphila was detected while disease-related Proteobacteria decreased. Stabilization of the microbiota took longer than expected from the rapidly improving clinical symptoms, suggesting the need for longer-lasting patient observation. The virome was mainly composed of Caudovirales bacteriophages but surprisingly also contained sequences related to a Chlorella giant virus that normally infects green algae not known to inhabitate the human intestine. FMT is highly effective against rCDI and is presently broadening its application to other conditions including inflammatory bowel disease (IBD). Here, we discuss the prospects and challenges of FMT against rCDI and other indications including a focus on bacteriophages.